In-situ observation of dislocation dynamics near heterostructured interfaces - Zhou, Hao; Huang, Chongxiang; Sha, Xuechao; Xiao, Lirong; Ma, Xiaolong; Höppel, Heinz Werner; Göken, Mathias; Wu, Xiaolei; Ameyama, Kei; Han, Xiaodong; Zhu, Yuntian (Materials Research Letters, 2019)
There has been a long-standing controversy on how dislocations interact with interfaces. Here we report in-situ observations that in a Cu-brass heterostructured TEM film Frank-Read sources are the primary dislocation sources. They were dynamically formed and deactivated throughout the deformation in grain interior, which has never been reported before. This observation indicates that strain gradient near interfaces cannot be quantitatively related to the density gradient of geometrically necessary dislocations, and it was primarily produced by Frank-Read source gradient instead of dislocation pile-ups. These findings provide new insights on how to design heterostructured interfaces to enhance mechanical properties.
CRIS-Team WoS Importer:2019-06-28